2013
DOI: 10.1155/2013/460927
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarumLG42 Isolated from Gajami Sik-Hae Inhibits Adipogenesis in 3T3-L1 Adipocyte

Abstract: We investigated whether lactic acid bacteria isolated from gajami sik-hae (GLAB) are capable of reducing the intracellular lipid accumulation by downregulating the expression of adipogenesis-related genes in differentiated 3T3-L1 cells. The GLAB, Lactobacillus plantarum LG42, significantly decreased the intracellular triglyceride storage and the glycerol-3-phosphate dehydrogenase (GPDH) activity in a dose-dependent manner. mRNA expression of transcription factors like peroxisome proliferator-activated receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 43 publications
4
28
0
1
Order By: Relevance
“…plantarum in FKS have acid and bile tolerance, antioxidative effects, and anti-proliferative effects on HT-29 human colorectal cancer cells (18). Also, anti-obesity effect of the above starters on 3T3-L1 cells and animals were previously reported (4,19,20). Lee et al (21) reported Leu.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…plantarum in FKS have acid and bile tolerance, antioxidative effects, and anti-proliferative effects on HT-29 human colorectal cancer cells (18). Also, anti-obesity effect of the above starters on 3T3-L1 cells and animals were previously reported (4,19,20). Lee et al (21) reported Leu.…”
Section: Resultsmentioning
confidence: 93%
“…plantarum has been reported to reduce adipogenesis and lipogenesis by inhibiting the activations of PPAR-, C/EBP, and FAS in 3T3-L1 adipocytes (19,20), Leuconostoc sp. and Lactobacillus sp.…”
Section: Kimchi Attenuated the Mrna Levels Of Ppar- C/ebp And Fasmentioning
confidence: 99%
“…[43][44][45][46][47] In accordance with this, L. plantarum LG42 isolated from gajami-sikhae showed probiotic effects including anti-obesity properties. 7,11) A strain of L. sakei isolated from another food had been evaluated for its probiotic potential such as gastric resistance, survival, and bacteriocin production in the presence of bile salts and commercial prebiotics, and reducing the adhesion of Listeria monocytogenes to intestinal epithelial cells. 48) Therefore, we need to characterize the L. sakei strain isolated from gajami-sikhae to determine its potential probiotic effects.…”
Section: Discussionmentioning
confidence: 99%
“…10) Lactobacillus plantarum LG42, a lactic acid bacterium (LAB), was isolated from gajami-sikhae and its antiobesity effect on high-fat-diet-induced obese mice was investigated. 7,11) The high-fat-diet-induced obese mice group supplemented with L. plantarum LG42 showed lower body weight and reduced epididymal and back fat as compared *Corresponding author. Email: lmk123@kfri.re.kr Abbreviations: ACC, acetyl CoA carboxylase; CPT-I, carnitine palmetonyltransferase-I; DGGE, denaturing gradient gel electrophoresis; LAB, lactic acid bacterium; LXRα, liver X receptor α; NGS, next-generation sequencing; OTU, operational taxonomic unit; PCoA, principal coordinate analysis; PPARα, peroxisome proliferator-activated receptor α; SREBP-1, sterol regulatory element-binding protein-1.…”
mentioning
confidence: 99%
“…While Kyoungsangdo-style recipes use dried Alaska pollock, undried fish are utilized for the Kangwondo-style recipes. Despite its importance as a Korean fermented food, there is limited research regarding sikhae and our understanding of the fermentation mechanisms of sikhae is largely incomplete.Novel bacterial strains were isolated from sikhae, mainly from gajami-sikhae (Kim et al, 2009;Jung et al, 2012a;Shin et al, 2011;Park et al, 2013Park et al, , 2014. Alishewanella jeotgali MS1 T was isolated from gajami-sikhae and its genome was fully sequenced (Kim et al, 2009;Jung et al, 2012a).…”
mentioning
confidence: 99%